Sex and relationships for HIV positive women since HAART: a quantitative study. Issue 4 (1st August 2005) - Lambert, S; Keegan, A; Petrak, J
Abstract : Objective: To investigate current levels of sexual activity, enjoyment, condom use, and other factors affecting sexual behaviour in a sample of women living with HIV. Method: Participants were self selected. A cross sectional design using semi-structured questionnaires was employed. 82 HIV positive women completed questionnaires asking about demographics, relationships, sexual behaviour, and safer sex practices. The Hospital Anxiety and Depression Scale (HADS) and Golombok-Rust Inventory of Sexual Satisfaction (GRISS) were administered. Results: 28% of women had had no sexual partners since diagnosis. Mean time diagnosed was 69 months, range 4–191 months. Time since diagnosis was not associated with having had a sexual partner. 59% of women had a current sexual partner, half reporting intercourse in the past month. Infrequent sex (84%), avoidance (84%), non-communication (69%), and dysfunction (60%) were among the most prevalent sexual difficulties. Endorsement of HIV impaired sexual enjoyment was associated with reduced sexual frequency (p = 0.006) and sexual dysfunction (p = 0.042). Sexual dissatisfaction was associated with infrequency of sex (p = 0.037), avoidance (p = 0.02), and non-communication (p = 0.032). Clinically significant levels of anxiety and depression were reported in 60% and 38% of cases, respectively. Depression was associated with avoidance of sex and higher total GRISS scores (p = 0.006 and p = 0.042). 60% of respondents stated that they "always" used condoms; a trend was observed between reduced condom use and higher levels of depression and anxiety (p = 0.09 and p = 0.06, respectively). Conclusion: Sexual difficulties, including abstinence, were prevalent in this sample indicating the potential for interventions addressing the psychosexual needs of HIV positive women and their partners.